2022
DOI: 10.1021/acsmeasuresciau.2c00017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Opto-electrochemical Differentiation of Marine Phytoplankton

Abstract: The use of electro-generated oxidants in seawater facilitates the discrimination of different plankton groups via monitoring the decay in real time of their chlorophyll-a (chl-a) fluorescence signals following potentiostatic initiation of electrolysis in their vicinity (Yang, M. et al. Chem. Sci.2019, 10(34), 7988−7993). In this paper, we explore the sensitivity of phytoplankton to different chemical species produced at various potentials in seawater. At low potentials, the oxidation of ca. millimolar bromide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The fluoro‐electrochemical measurements were made as follows ( see Fig. 1a, adapted from Yu et al 2022): A concentrated sample from a phytoplankton monoculture in exponential growth phase (as described in the Culturing for the “susceptibility library” section) was “drop cast” onto the surface of the working electrode. After ~ 1 min of allowing the cells to be deposited on the surface, excess solution was gently drawn‐off using a tissue.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The fluoro‐electrochemical measurements were made as follows ( see Fig. 1a, adapted from Yu et al 2022): A concentrated sample from a phytoplankton monoculture in exponential growth phase (as described in the Culturing for the “susceptibility library” section) was “drop cast” onto the surface of the working electrode. After ~ 1 min of allowing the cells to be deposited on the surface, excess solution was gently drawn‐off using a tissue.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…( a ) a simple schematic diagram of the electrochemistry—fluorescence microscope set up adapted from Yu et al (2022); ( b ) an example of normalized Chl a fluorescence transient data for the species Phaeocystis globosa , following onset of the potential (at time 0 s) and with a current ramping of 10 μ A s −1 . Each black line represents a single cell measurement ( n = 110), and the dashed red markings highlight the time point, t 50 , where normalized fluorescence values have been reduced by 50%.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…16 More importantly, it has been reported that although different life-stages coexisted within the population of a species of marine green algae, Chlamydomonas concordia, the size-normalized susceptibility was not affected by its life stages. 17,18 However, considering the vast number of phytoplankton species in the contemporary ocean (∼5000), 19 systematically classifying them using a single susceptibility parameter is challenging.…”
Section: Introductionmentioning
confidence: 99%